Low Nitrous Oxide Emissions in a Boreal Spruce Forest Soil, Despite Long-Term Fertilization - Rütting, Tobias; Björsne, Anna-Karin; Weslien, Per; Kasimir, Åsa; Klemedtsson, Leif (Frontiers in Forests and Global Change, 2021)
Nitrogen (N) fertilization can increase stem wood production by several hundred percent in boreal forests. At the same time, there are concerns about the environmental consequences of N fertilization, especially considering losses of the greenhouse gas nitrous oxide (N2O) to the atmosphere. Soils are a large contributor to N2O emissions on a global scale. The aim of this study was to investigate the consequences of long-term nutrient optimization fertilization on N2O emissions in a boreal forest in Northern Sweden. Field N2O flux measurements were conducted during two years with manual and automatic chambers, as well as gas probes in the snow. The N2O emissions were generally low during the whole period of measurements, both from the control and fertilized plots. The emissions were generally highest during the winters, as well as the variability in the observed values. Overall, N2O emissions from fertilized plots were about twice the control, which could be explained by changes in the soil carbon-to-nitrogen ratio.